PENDIDIKAN TAUHID DAN AKIDAH PADA ANAK DENGAN MEMBANGUN CINTA PADA ISLAM - Umi Kalsum; Zulkarnen Zulkarnen (Institut Dirosat Islamiyah Al-Amien Prenduan, 2022)
Monotheism and faith education is primary education that must be taught to children early. Parents are the most crucial foundation in children's behaviour and language. This monotheistic education is given to make children servants of Allah, who will limit all His commands and prohibitions and become people who are helpful to society and its people. Parents can teach their children through habituation or best practice because children prefer to follow what they see, not what they hear. Of course, as role models in children's lives, parents must provide examples that develop values. Monotheism and faith in children so they can feel the love of Islam within themselves.